1998
DOI: 10.1021/cm970618g
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity Enhancement by Solid-State Proton Transfer: A New Strategy for the Design of Nonlinear Optical Materials

Abstract: Theoretical considerations of the molecular hyperpolarizabilities (β) of donor-acceptor substituted aromatic molecules show that the transfer of a proton from the electron-donor group of an acid to the electron acceptor group of a base could increase β for both resulting ionic species relative to the corresponding neutral molecules. To take advantage of this, the cocrystallization of 4-nitrophenol with various organic bases was studied. Cocrystallization of 4-nitrophenol with 4-(dimethylamino)pyridine gives ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 53 publications
(40 reference statements)
5
72
0
Order By: Relevance
“…Evans et al [10] demonstrated the utilization of acid/base proton transfer to enhance the hyperpolarizabilities of the chromophores and our calculations show also an increase of the component β zzz upon protonation. If we consider the interaction between the cations and anions there is a further increase in the molecular NLO properties.…”
Section: Calculated Microscopic Nlo Propertiessupporting
confidence: 66%
See 1 more Smart Citation
“…Evans et al [10] demonstrated the utilization of acid/base proton transfer to enhance the hyperpolarizabilities of the chromophores and our calculations show also an increase of the component β zzz upon protonation. If we consider the interaction between the cations and anions there is a further increase in the molecular NLO properties.…”
Section: Calculated Microscopic Nlo Propertiessupporting
confidence: 66%
“…These systems exhibit high nonlinear optical efficiency in the visible region and good thermal and mechanical stability compared with those of purely organic crystals. Besides these advantages, it was demonstrated by Evans et al [10] that the proton transfer occurring in acid/base reactions, often used to synthesize these hybrid materials, can enhance the hyperpolarizabilities of the chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, many approaches have been developed to acquire noncentrosymmetric crystals [17][18][19][20] in which one way to include both ionic and hydrogen-bonding interactions in a system is to form ionic co-crystals from proton transfer between an organic acid and organic base [21][22][23]. 4-nitrophenolate (NP-) with a typical one-dimensional (1D) donor-acceptor p system and the proton transfer of phenolic OH with various organic and inorganic bases results in the increasing of hyperpolarizability of both species has been used to form a large number of noncentrosymmetric structures with the achiral counterions [24][25][26][27][28][29][30]. Pyridine is a good hydrogen-bond acceptor and a strong organic base.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover if a proton transfer between two separate NLO organic chromophores takes place and result in a non-centrosymmetric organic salt, then this could increase the hyperpolarisability of both species, provided one being an acid and second being a base. This first purposeful utilization of this strategy (proton transfer) to increase the hyperpolarizabilities of the chromophores was proposed by Evans and his co-workers [11] and they have reported the crystal structure and SHG signal test of the title compound dimethyl amino pyridinium-4 nitro phenolate 4-nitro phenol (DMAPNP). The title compound was synthesized and reported by Huang et al [9].…”
Section: Introductionmentioning
confidence: 99%